The effect of erbium, chromium:yttrium-scandium-gallium-garnet (Er,Cr:YSGG) laser therapy on pain during cavity preparation in paediatric dental patients: a pilot study - (:unkn) unknown (My University, 2013)
INTRODUCTION: Standard treatment for caries removal and cavity preparation for restorations using mechanical means is often accompanied by fear and pain for the patient. Although the pain may be reduced by local anaesthesia, fear of the needle, noise, and the vibration of mechanical preparation remain a cause of discomfort. Erbium, chromium:yttriumscandium- gallium-garnet (Er,Cr:YSGG) laser irradiation indicates that pain perception may be reduced relative to that caused by mechanical preparation. AIM: The aim of this pilot clinical study was to perform a preliminary evaluation of pain perception during cavity preparation comparing the mechanical removal and Er,Cr:YSGG laser removal of caries from enamel and dentine. METHODS: The study sample was ten children aged 7 to 12 years. Half of the preparations were completed by the laser alone and the other half were mechanically prepared. All cavities were restored with light-cured composite resin following the application of acid etch and a bonding agent. The time spent on cavity preparation and the behaviour of the patients during cavity preparation were recorded. Children were instructed to rate their pain on a visual analogue scale. In addition, the patients were asked to decide which was the more uncomfortable form of treatment and the preferred treatment for future caries therapy. RESULTS: Children showed considerably more body and head movement with the conventional mechanical preparation. The subjects rated the perception of pain lower when the laser technique was used. CONCLUSION: In the small number of children studied, the application of the Er,Cr:YSGG laser system was a more comfortable alternative or adjunctive method to conventional mechanical cavity preparation. A far larger study is necessary to confirm this finding.
Keywords: Humans; Child; Dental Caries; Time Factors; Dental Materials; Pilot Projects; Pain Measurement; Composite Resins; Child Behavior; Dental Bonding; Dental Cavity Preparation; Dental Restoration, Permanent; Head Movements; Laser Therapy; Lasers, Solid-State; Pain Perception